2007
DOI: 10.1111/j.1463-1318.2007.01424.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic response assessed by Mandard grade is a better prognostic factor than down staging for disease‐free survival after preoperative radiochemotherapy for advanced rectal cancer

Abstract: Tumour regression of grades I or II was a good indicator of DFS in locally advanced rectal cancer, treated by neoadjuvant chemotherapy and radiotherapy. Patients with a high regression grade were associated with a lower incidence of definitive stoma formation. The regression grade was shown to be a better prognostic factor than down-staging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 33 publications
6
88
1
5
Order By: Relevance
“…pTR was defined as Mandard Tumor Regression Grade (TRG) of 3 or less, after dedicated review by a consultant cellular pathologist (27). The Mandard TRG was used in preference to alternative TRGs, being the most frequently used TRG for esophageal cancer (28), with optimal prediction of survival (29,30).…”
Section: Data and Variablesmentioning
confidence: 99%
“…pTR was defined as Mandard Tumor Regression Grade (TRG) of 3 or less, after dedicated review by a consultant cellular pathologist (27). The Mandard TRG was used in preference to alternative TRGs, being the most frequently used TRG for esophageal cancer (28), with optimal prediction of survival (29,30).…”
Section: Data and Variablesmentioning
confidence: 99%
“…Histopathologists grade tumour response in three ways: firstly assessment of the status of the CRM, secondly the depth of tumor spread and nodal status (ypT and ypN stage), and thirdly by evaluating tumor regression grade (ypTRG) [10,11]. A number of studies have shown that both ypT and ypN stage are independent predictors of outcome, and several retrospective studies report a link between outcome and histopathology assessment of final stage or tumor regression after NACRT [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…While other studies in rectal cancer patients with chemoradiation showed a downstaging rate between 43.5 and 60.4% [26,27,33], in the present study, a remarkable 81.8% of the patients reduced their tumor stage, which correlated with a significant shrinking of the tumor (90.9%). Therefore, EB treatment of these patients does not seem to promote tumor growth when anemia correction is achieved following current guidelines.…”
Section: Resultsmentioning
confidence: 50%
“…Moreover, treatment with EB was able to elude preoperative anemia in patients with levels of Hb B 11 g/dl without greatly interfering in the rate of surgical complications usually encountered in this setting, either in alpha-epoetin-treated patients (16%) [25] or regardless of hematopoietic correction (27.7-31.2%) [26,27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation